2001
DOI: 10.1093/carcin/22.8.1231
|View full text |Cite
|
Sign up to set email alerts
|

Presence of benzo[a]pyrene diol epoxide adducts in target DNA leads to an increase in UV-induced DNA single strand breaks and supF gene mutations

Abstract: Exposure to DNA damaging agents and mutagens often occurs as combinations of agents, or as complex mixtures of chemicals. We found that plasmid DNA adducted with benzo[a]pyrene diol epoxide (BPDE) was more susceptible to UV-induced single strand breaks than was control DNA. To determine whether the increase in DNA damage also applied to mutagenic lesions, the supF gene forward mutation assay was used to compare mutations induced by BPDE alone, UVB, UVC, BPDE followed by UVB and BPDE followed by UVC. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
3
15
1
Order By: Relevance
“…Only when that adducted DNA was UVC-irradiated were strand breaks induced, at a much greater frequency than in unadducted UVC-irradiated plasmid. As in this report we have not found evidence of the enhancement of oxidative DNA damage in cells exposed to BP and UVC, it may be that the additional strand breaks and mutations previously observed in plasmid DNA [Routledge et al, 2001] are due to sensitization of the DNA to UVinduced strand breakage.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Only when that adducted DNA was UVC-irradiated were strand breaks induced, at a much greater frequency than in unadducted UVC-irradiated plasmid. As in this report we have not found evidence of the enhancement of oxidative DNA damage in cells exposed to BP and UVC, it may be that the additional strand breaks and mutations previously observed in plasmid DNA [Routledge et al, 2001] are due to sensitization of the DNA to UVinduced strand breakage.…”
Section: Resultscontrasting
confidence: 66%
“…Strand breaks induced by BP in the alkaline comet assay are probably induced during the repair of BPDE adducts by the cells. In a previous study [Routledge et al, 2001], it was found that BPDE adduction of naked plasmid DNA did not itself induce DNA strand breaks as measured by the plasmid strand-break assay, which occurs in the absence of DNA repair. Only when that adducted DNA was UVC-irradiated were strand breaks induced, at a much greater frequency than in unadducted UVC-irradiated plasmid.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This assay is, however, not site specific as it involves treating a double stranded plasmid with a reactive compound to generate an array of adducts at a variety of positions throughout the plasmid. The assay does detect 97% of possible base substitutions within the 85 bp supF gene (22) as well as deletions and insertions and because the plasmid is treated in vitro , aliquots of the treated DNA can be analysed for adduct quantification in parallel to the mutation assay. The supF gene is however, a non-essential sequence, so any mutations which are induced would not affect the cell survival or other pathways of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It can be deduced, from the few data available on hydrocarbon body burdens, that PAH are rapidly metabolised and excreted from the body, and therefore PAH themselves do not persist for long time periods. During metabolism, PAH moieties can become covalently bound to tissue constituents such as proteins and nucleic acids (Routledge et al, 2001). Protein-bound metabolites are likely to persist, therefore, for periods that do not exceed the normal lifetime of the protein itself.…”
mentioning
confidence: 99%